The Effect of Training and Teamwork on Employee Performance at BASARNAS in North Maluku Province - Indriyani, Indriyani; Nurlaila, Nurlaila; Buamonabot, Irfandi (International Journal of Business, Law, and Education, 2026)
This study aims to examine the effect of training and teamwork on employee performance at BASARNAS in North Maluku Province, both partially and simultaneously. This research applies a quantitative approach, with data collected through questionnaires distributed to 93 respondents. The data were analyzed using SPSS through data quality testing, classical assumption testing, and multiple linear regression analysis. The results of the F-test indicate that training and teamwork simultaneously have a significant effect on employee performance, with a significance value below 0.05. Furthermore, the t-test results reveal that training has a positive and significant effect on employee performance, and teamwork also shows a positive and significant influence. This indicates that both variables contribute meaningfully to improving employee performance. In conclusion, this study highlights that enhancing training effectiveness and strengthening teamwork are essential strategies to improve employee performance and organizational productivity at BASARNAS in North Maluku Province.